2021
DOI: 10.1101/2021.01.05.21249190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host genome analysis of structural variations by Optical Genome Mapping provides clinically valuable insights into genes implicated in critical immune, viral infection, and viral replication pathways in patients with severe COVID-19

Abstract: BackgroundThe varied clinical manifestations and outcomes in patients with SARS-CoV-2 infections implicate a role of host-genetics in the predisposition to disease severity. This is supported by evidence that is now emerging, where initial reports identify common risk factors and rare genetic variants associated with high risk for severe/ life-threatening COVID-19. Impressive global efforts have focused on either identifying common genetic factors utilizing short-read sequencing data in Genome-Wide Association… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 96 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Given our findings of a protective role for membrane-anchored mucins against SARS-CoV-2, the development of therapeutics broadly antagonizing mucin expression should be pursued with caution. Structural variant studies of COVID-19 cases identified MUC4 loss-of-function to be associated with increased disease severity (Reay et al, 2021;Sahajpal et al, 2021). A more selective strategy promoting membrane-tethered mucins or reducing the secretion of gel-forming mucins may be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Given our findings of a protective role for membrane-anchored mucins against SARS-CoV-2, the development of therapeutics broadly antagonizing mucin expression should be pursued with caution. Structural variant studies of COVID-19 cases identified MUC4 loss-of-function to be associated with increased disease severity (Reay et al, 2021;Sahajpal et al, 2021). A more selective strategy promoting membrane-tethered mucins or reducing the secretion of gel-forming mucins may be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The identified structural variants were compared with the normal population by calculating the ratios to top-ranked genes. This study determined and confirmed the direct impact of some genes on the severity of disease in infected patients, and concluded that optical genome mapping is an efficient method to determine SARS-CoV-2 structural variants that help in the determination of disease outcome and mortality [ 96 , 97 ]. Recently, a patient-center-based investigation has identified 38 genes which are directly linked to different host–viral association pathways: innate/inflammatory immune responses, passage resistance, viral propagation, RNA editing and viral spread.…”
Section: Host Genetic and Epigenetic Machineries In Covid-19 And Thei...mentioning
confidence: 92%
“…However, to resolve this issue, several advanced technologies have been utilized, such as optical genome mapping using BioNano’s Saphyr ® system (BioNano Genomics, CA, USA). By this technology, SARS-CoV-2-associated structural variants were identified in 37 hospitalized infected individuals [ 96 ]. Furthermore, the variants’ specific small or rare structural changes were analyzed in a similar group of patients by whole-genome sequencing analysis.…”
Section: Host Genetic and Epigenetic Machineries In Covid-19 And Thei...mentioning
confidence: 99%